Factors Affecting the Use of Pain-Coping Strategies in Individuals with Cerebral Palsy and Individuals with Typical Development - Inmaculada Riquelme; Pedro Montoya (MDPI AG, 2023)
Many individuals with cerebral palsy (CP) suffer from pain and must develop pain-coping strategies, although the factors determining them are unknown. This observational study aims at exploring the association between different pain-coping strategies and factors such as age, sex, pain, health status, sleep or motor and cognitive function in individuals with cerebral palsy (CP) and typically developing peers (TD). Main caregivers of 94 individuals with CP (age range = 6-69 years, mean age = 17.78 (10.05)) and the closest relative of 145 individuals with TD (age range = 6-51 years, mean age = 19.13 (12.87)) completed questionnaires on the previous topics (Parent Report of the PEDsQL Pediatric Coping Inventory, the Health Utility Index HUI-3, Epworth Sleepiness Score and the Pittsburgh Sleep Quality Index). Pain presence, duration, intensity, location and ratings of current and worst pain in the last week in an 11-point numerical rating scale were assessed in an interview. Global health was the best predictor the of use of any type of pain-coping strategy, including cognitive self-instruction, problem-solving, distraction, seeking social support and catastrophizing, in both individuals with CP and individuals with TD. However, different health attributes predicted their use in each population. Emotional health was the best predictor in individuals with CP, whereas cognition and pain were the best predictors in individuals with TD. Speech ability was a predictor in both groups. In conclusion, the assessment of health attributes such as emotional health and speech may help design specific interventions for enhancing self-efficacy and adaptive pain coping skills.